Evaluation of cytochrome P-450 concentration in Saccharomyces cerevisiae strains - Míriam Cristina Sakuragui Matuo; Irene Satiko Kikuchi; Terezinha de Jesus Andreoli Pinto (Universidade de São Paulo, 2010)
Saccharomyces cerevisiae has been widely used in mutagenicity tests due to the presence of a cytochrome P-450 system, capable of metabolizing promutagens to active mutagens. There are a large number of S. cerevisiae strains with varying abilities to produce cytochrome P-450. However, strain selection and ideal cultivation conditions are not well defined. We compared cytochrome P-450 levels in four different S. cerevisiae strains and evaluated the cultivation conditions necessary to obtain the highest levels. The amount of cytochrome P-450 produced by each strain varied, as did the incubation time needed to reach the maximum level. The highest cytochrome P-450 concentrations were found in media containing fermentable sugars. The NCYC 240 strain produced the highest level of cytochrome P-450 when grown in the presence of 20 % (w/v) glucose. The addition of ethanol to the media also increased cytochrome P-450 synthesis in this strain. These results indicate cultivation conditions must be specific and well-established for the strain selected in order to assure high cytochrome P-450 levels and reliable mutagenicity results. Linhagens de Saccharomyces cerevisiae tem sido amplamente empregadas em testes de mutagenicidade devido à presença de um sistema citocromo P-450 capaz de metabolizar substâncias pró-mutagênicas à sua forma ativa. Devido à grande variedade de linhagens de S. cerevisiae com diferentes capacidades de produção de citocromo P-450, torna-se necessária a seleção de cepas, bem como a definição das condições ideais de cultivo. Neste trabalho, foram comparados os níveis de citocromo P-450 em quatro diferentes linhagens de S. cerevisiae e avaliadas as condições de cultivo necessárias para obtenção de altas concentrações deste sistema enzimático. O maior nível enzimático foi encontrado na linhagem NCYC 240 em presença de 20 % de glicose (p/v). A adição de etanol ao meio de cultura também produziu um aumento na síntese de citocromo P-450. Estes resultados indicam que as condições de cultivo devem ser específicas e bem definidas para a linhagem selecionada, garantindo assim elevados níveis de citocromo P-450 e, conseqüentemente, a confiabilidade nos testes de mutagenicidade.